Pengembangan Standar dan Pedoman Penilaian Soft Skill Perawat - Riawan, Deffy Lettyzia; Chalidyanto, Dhazuly; Palupi, Aprilia Laksmi; Rahmawati, Nanda Annisa; Qualisa, Prafidina; Ongko, Tjindrawati; Yudhistira, Dhau' Atha (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to develop standards and guidelines for assessing the soft skills of nurses at PHC Hospital Surabaya, in order to enhance professional interaction and the quality of patient care. A descriptive cross-sectional approach was used with stratified random sampling of nursing professionals actively involved in the Inpatient, Outpatient, and Medical units. Data collection included quantitative metrics from historical assessments, qualitative insights from Focus Group Discussions (FGD), and a literature review. The method used was a 360-degree evaluation, involving supervisors, colleagues, subordinates, and self-assessment. The results showed significant deficiencies in critical soft skills such as communication, teamwork, leadership, empathy, decision-making, and adaptability. The assessment revealed that no soft skills met the hospital's standards, with all scores below the 80% threshold considered very good. The highest levels of soft skills were observed in communication and interpersonal skills, though only 26.0% were rated as sufficient. The acronym